2021
DOI: 10.1557/s43578-020-00094-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and applications of fullerene-based metal nanocomposites: A review

Abstract: Several fabrication methods have been proposed to develop the metal matrix nanocomposites (MMNCs) reinforced by carbon nanomaterials (mostly the nanotubes, and graphene) by means of the liquid-state and the solid-state techniques. The spraying processes, the squeeze casting, the disintegrated melt deposition processes, the milling fabrication, and the friction stir processing have been used to fabricate the composite. However, the MMNCs, containing the fullerenes as reinforcement, are less known, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Moreover, fullerenes are highly pure and maintain their quality over time. As a result, fullerenes are currently under investigation and have potential applications in various technical fields (Joshi & Mehta, 2021 ). Metallic alloys are likely to use fullerenes for reinforcement in structural parts as an important application.…”
Section: Nanotechnologymentioning
confidence: 99%
“…Moreover, fullerenes are highly pure and maintain their quality over time. As a result, fullerenes are currently under investigation and have potential applications in various technical fields (Joshi & Mehta, 2021 ). Metallic alloys are likely to use fullerenes for reinforcement in structural parts as an important application.…”
Section: Nanotechnologymentioning
confidence: 99%
“…However, it is observed that fullerene may be considered as fascinating reinforcements in comparison to CNT or graphene due to their zero-dimensional structure of carbon molecules, which exist in the form of spherical, tube shape and ellipsoid. The fullerene related to C 60 is called Bucky ball or Buckminster fullerene spherical in shape, which corresponds to a soccer ball [49,[54][55][56]. The carbon nanotubes (CNTs) [57][58][59][60][61] a new allotrope of carbon is normally thin hollow cylindrical fullerene structure in the diameter of nano-scale range and little micron length with significant properties.…”
Section: Different Carbon Based Nanofillers Reinforced Epoxy Compositesmentioning
confidence: 99%
“…The contemporary demand for the development of lightweight hybrid composite materials with high specific strength, stiffness and improved tribological performance for end used applicability in the areas of aerospace and automotive industries [49,56,68]. During the past few times, fullerene and fullerene-based composites have been synthesized and used in various applications particularly in the thin films, organic polymers and hybrid organic-inorganic composites in the field of microelectronics [68].…”
Section: Fullerene Reinforced Epoxy Compositesmentioning
confidence: 99%
See 1 more Smart Citation